2018
DOI: 10.1080/02699052.2017.1419377
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of agitation among individuals with moderate to severe acquired brain injury: A systematic review

Abstract: Studies consistently demonstrated that pharmacological treatment was effective in reducing agitation post ABI; however, there was insufficient information to develop a conclusion due to the limited number of studies and overall weakness of evidence for each individual medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…With respect to the findings from previous reviews, all have agreed that no strong conclusions could be drawn due to the limited number of studies and overall weakness of the evidence for each class of medication (34, 39, 41). Notwithstanding this, there was a general consensus that the current best evidence for treatment of aggression post TBI supports the use of amantadine and beta-blockers, with typical neuroleptics only to be prescribed with caution due to concern regarding adverse events (34, 36, 38, 41, 42, 4447). Many other drugs have also been listed as possible options including anticonvulsants (mostly carbamazepine, valproic acid), specific serotonin reuptake inhibitors (SSRIs), tricyclic antidepressants (TCA), atypical antipsychotics, methylphenidate, and lithium (4042, 44, 46, 47).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…With respect to the findings from previous reviews, all have agreed that no strong conclusions could be drawn due to the limited number of studies and overall weakness of the evidence for each class of medication (34, 39, 41). Notwithstanding this, there was a general consensus that the current best evidence for treatment of aggression post TBI supports the use of amantadine and beta-blockers, with typical neuroleptics only to be prescribed with caution due to concern regarding adverse events (34, 36, 38, 41, 42, 4447). Many other drugs have also been listed as possible options including anticonvulsants (mostly carbamazepine, valproic acid), specific serotonin reuptake inhibitors (SSRIs), tricyclic antidepressants (TCA), atypical antipsychotics, methylphenidate, and lithium (4042, 44, 46, 47).…”
Section: Introductionmentioning
confidence: 96%
“…Pharmacological methods are more commonly used. Given there are no FDA (Food and Drug Administration) approved medications for aggression post TBI, all medication is prescribed off-label (34, 35). As such, clinicians must rely on their clinical expertise, experience in treating similar conditions, extrapolation of aggression management from non-TBI populations, and consideration of other factors that may preclude certain medications such as availability and cost (34, 36).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Evidence on pharmacological intervention for post-TBI aggression Since Deb and Crownshaw's 9 original systematic review on the effectiNeuropsychiatry Inventory-Aggressionveness of psychotropics on neurobehavioural symptoms of TBI, several reviews have been published on this. [10][11][12][13][14][15][16][17][18][19] Findings from all the RCTs on pharmacotherapy for post-TBI aggression are summarised in table 2. A number of studies have shown methylphenidate's (MPH) effectiveness in improving post-TBI cognitive impairment and sometimes apathy symptoms.…”
mentioning
confidence: 99%